2021
DOI: 10.21037/atm-21-2823
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of EGFR T790M-mutant non-small cell lung cancer with almonertinib after osimertinib-induced interstitial lung disease: a case report and literature review

Abstract: Third-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) have revolutionized the standard treatment for EGFR T790M-positive non-small cell lung cancer (NSCLC). Osimertinib is one of the third-generation EGFR-TKIs and is currently the most advanced in clinical development. Interstitial lung disease (ILD) is a potentially fatal side effect of osimertinib use.Successful rechallenge with the second-generation TKI afatinib following osimertinib-induced ILD has been reported. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In a case report by Shen et al ( 20 ), almonertinib overcame osimertinib resistance associated with the L718Q mutation in a patient with metastatic NSCLC. Wu et al ( 21 ) and Zhang et al ( 22 ) reported successful treatment with aumolertinib after osimertinib-induced interstitial lung disease and cardiotoxicity. These results suggested a potential agent for reversing drug osimertinib-resistance and indicated a better safety profile for aumolertinib compared with that for osimertinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case report by Shen et al ( 20 ), almonertinib overcame osimertinib resistance associated with the L718Q mutation in a patient with metastatic NSCLC. Wu et al ( 21 ) and Zhang et al ( 22 ) reported successful treatment with aumolertinib after osimertinib-induced interstitial lung disease and cardiotoxicity. These results suggested a potential agent for reversing drug osimertinib-resistance and indicated a better safety profile for aumolertinib compared with that for osimertinib.…”
Section: Discussionmentioning
confidence: 99%
“…One is that aumolertinib carries lower half maximal inhibitory values for T790M and L858R mutations, and T790M and Del 19 mutations, respectively, than osimertinib (i.e., 0.29 vs. 0.46 nmol/l, and 0.21 vs. 0.29 nmol/l) ( 23 ). The other is that aumolertinib may partly overcome the drug resistance of osimertinib in advanced NSCLC ( 21 ). Finally, the mean plasma concentration of aumolertinib (110 mg/day) is slightly higher than that of osimertinib (80 mg/day) (155.5 vs. 138.98 ng/ml) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Almonertinib has high selectivity to EGFR‐sensitizing mutation and T790M‐resistance mutation and also has good central nervous system activity (Yang et al, 2020). Moreover, it effectively blocks the production of non‐selective active metabolite AZ5104 and has significantly improved safety compared with osimertinib (Nagasaka et al, 2021; Wu, Zhong, et al, 2021). Almonertinib is a moderately sensitive substrate of CYP3A4 in vivo and mainly metabolized to HAS‐719 in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Once pneumonitis occurs, the permanent discontinuation of MET inhibitors and corticosteroid treatment have been suggested [ 6 ]. Other types of target agents within the same class have been used after drug-induced pneumonitis in patients receiving EGFR-TKI [ 9 , 10 , 11 ] and ALK inhibitors [ 12 ]. However, the safety of using another MET inhibitor after discontinuing the first remains largely unknown and such patients have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%